Association of Transforming Growth Factor Alpha and Methylenetetrahydrofolate reductase gene variants with nonsyndromic cleft lip and palate in the Indian population - Desai, Asavari L. (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVES: The aim was to evaluate the relationship of the K-primer variant of the transforming growth factor-alpha (TGF-α) gene and C677T variant of the methylenetetrahydrofolate reductase (MTHFR) gene with nonsyndromic cleft lip and palate (CL/P) in the Indian population. SETTING AND SAMPLE POPULATION: The study group consisted of DNA samples of 25 subjects with nonsyndromic CL with or without cleft palate and 25 unrelated controls, already existing in the Department of Orthodontics, D.A.P.M.R.V. Dental College, Bengaluru, Karnataka, India. MATERIALS AND METHODS: The DNA samples were divided into two categories: Group A which included the 25 subjects with nonsyndromic CL/P; and Group B, which consisted of the 25 unrelated controls. The polymerase chain reaction (PCR) test was done for amplification of the region of interest from the DNA samples. Restriction digestion was then performed on the amplified product using the restriction enzyme HinfI, separately for each of the variants. The digested PCR products were separated into channels on a 1.5% agarose gel containing ethidium bromide in an electrophoretic chamber. A U.V. transilluminator was used to see the specific bands of base pairs of the digested PCR products. RESULTS: In Group A, the TGF-α gene variant was present in 16 subjects (P = 0.001) and MTHFR gene variant was present in 8 subjects (P = 0.185). A combination of both gene variants were present in seven subjects, which was an interesting finding. In Group B, four subjects tested positive for the TGF-α and MTHFR gene variants. CONCLUSIONS: The TGF-α gene variant and a combination of TGF-α + MTHFR gene variants significantly contribute to the development of nonsyndromic CL/P and can be considered as genetic markers for Indian population. The MTHFR gene variant, though a minor risk factor, cannot be considered as a genetic marker.